Cation non-stoichiometry in Fe:SrTiO3 thin films and its effect on the electrical conductivity. Issue 21 (22nd September 2021) - Morgenbesser, Maximilian; Taibl, Stefanie; Kubicek, Markus; Schmid, Alexander; Viernstein, Alexander; Bodenmüller, Niklas; Herzig, Christopher; Baiutti, Federico; de Dios Sirvent, Juan; Liedke, Maciej Oskar; Butterling, Maik; Wagner, Andreas; et al.
Abstract : The interplay of structure, composition and electrical conductivity was investigated for Fe-doped SrTiO3 thin films prepared by pulsed laser deposition. Abstract : The interplay of structure, composition and electrical conductivity was investigated for Fe-doped SrTiO3 thin films prepared by pulsed laser deposition. Structural information was obtained by reciprocal space mapping while solution-based inductively-coupled plasma optical emission spectroscopy and positron annihilation lifetime spectroscopy were employed to reveal the cation composition and the predominant point defects of the thin films, respectively. A severe cation non-stoichiometry with Sr vacancies was found in films deposited from stoichiometric targets. The across plane electrical conductivity of such epitaxial films was studied in the temperature range of 250–720 °C by impedance spectroscopy. This revealed a pseudo-intrinsic electronic conductivity despite the substantial Fe acceptor doping, i.e. conductivities being several orders of magnitude lower than expected. Variation of PLD deposition parameters causes some changes of the cation stoichiometry, but the films still have conductivities much lower than expected. Targets with significant Sr excess (in the range of several percent) were employed to improve the cation stoichiometry in the films. The use of 7% Sr-excess targets resulted in near-stoichiometric films with conductivities close to the stoichiometric bulk counterpart. The measurements show that a fine-tuning of the film stoichiometry is required in order to obtain acceptor doped SrTiO3 thin films with bulk-like properties. One can conclude that, although reciprocal space maps give a first hint whether or not cation non-stoichiometry is present, conductivity measurements are more appropriate for assessing SrTiO3 film quality in terms of cation stoichiometry.